Deploying artifical intelligence techniques in loan application processing - Siraj, Fadzilah; Yusoff, Nooraini (2005)
The granting of loans by a financial institution is one of the important decisions that require insubstantial care. The institution usually employs loan officers to make credit decisions or recommendations for that particular institution. These officers are given some hard roles in evaluating the worthiness of each application. Some researchers recognize that the capability of humans to judge the worthiness of a loan is rather poor. Since business data warehouses store historical data from previous application, it is likely that there is knowledge hidden in this data may be useful in decision making. Unfortunately the task of discovering hidden information and useful relationship from data is difficult for human. This is due the fact that the data to be examined is very large and the nature of the relationship within the data is not obvious. To this end, Artificial Intelligence (AI) techniques can be beneficial to assist the decision maker in making decisions regarding loan application. AI provides a variety of useful tool for discovering the non-obvious relationships in historical data, while ensuring those relationships discovered will generalize to the future data. This knowledge is important and can be used by the loan officer in determining whether to accept or reject an application. This study suggests that loan application processing system integrates two components of computer-based information system namely, office automation system and AI system that comprises of intelligent decision support system and knowledge based system. In essence, the potential use of such a system can be accelerated to promote any organizations as an efficient and effective organization that has competitive advantage.